Bananas and Food security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Bananas and Food security Proceedings of an international symposium held in Douala, Cameroon, 10 14 November 1998. In English and French.